Prostanoid and TP-receptors in atherothrombosis: Is there a role for their antagonism? - Giannarelli, Chiara; Zafar, M. Urooj; Badimon, Juan J. (Thrombosis and Haemostasis, 2010)
Atherosclerosis and its clinical manifestations (i.e. myocardial infarction, stroke) are major causes of mortality and morbidity in Western countries. Endothelial dysfunction is considered the first step in the cascade leading up to coronary events. Increasing evidence suggests that direct inhibition of thromboxane A2/prostaglandin (TP)-receptors may not only have anti-platelet effects but also impact endothelial dysfunction as well as inflammatory component of atherosclerosis. While TP-receptor involvement in platelet function has received the greatest attention, more recent findings support the critical role of TP-receptor in other pathophysiological aspects of atherothrombosis. Prostanoids (i.e. TxA2, F2-isoprostanes, prostaglandins endoperoxides PGG2/PGH2) are known to promote the initiation and progression of atherosclerosis, not only via platelet activation, but through leukocyte-endothelial interactions and vasoconstriction. Dysfunctional endothelium, characterised by increased COX-activity, releases prostanoids that promote endothelial exposure to adhesion molecules and induce smooth muscle cell contraction. Plaque macrophages synthesise PGH2/PGG2 via COX-2; these potent prostanoids can trigger platelet activation and aggregation despite COX-1 inhibition by aspirin. TP-receptor inhibition has been reported to exert anti-atherosclerotic effects in pre-clinical model of disease. Reduction of plaque burden was associated with plaque stabilisation documented by the reduction in the content of macrophages, apoptotic cells, MMPs and endothelin-1, and the increase in smooth muscle cells content. TP-receptor blockade might have an anti-athero-sclerotic and plaque stabilisation effect. The possibility of combining anti-platelet activity with an anti-atherosclerotic effect via selective TP-receptor inhibitors could have important implications especially in clinical conditions associated with increased production of prostanoids, such as diabetes.
Keywords: Atherothrombosis; endothelial cells; platelet physiology; prostanoids; TP-receptors